Upaya Guru TPA dalam Meningkatkan Kemampuan Baca Al-Qur’an di Taman Pendidikan Al-Qur’an Babussalam Jorong Simpang Pogang - Azhari, Dea; Husni, Arman; Salmiwati, Salmiwati; Arifmiboy, Arifmiboy (Lembaga Yasin AlSys, 2023)
The author's motivation in choosing this is because the author sees students who have low Al-Qur'an reading skills, as well as a lack of student interest in learning so that it makes students play games and joke around and go in and out during learning which of course affects reading ability. child. So that in this case the efforts of a teacher are needed in improving the ability to read the Koran. This type of research is a type of field research that is qualitative in nature which is obtained through observations and interviews with teachers of the Babussalam Qur'an Education Center, which produces descriptive data in the form of spoken words, writing, and observed behavior of the subjects studied. . This research only provides an overview of the efforts made by Babussalam Al-Qur'an Education Park teachers in improving children's ability to read the Al-Qur'an. Based on the results of the research conducted by the author, it can be seen that the efforts made by the teacher at the Babussalam Al-Qur'an Education Center in improving children's Al-Qur'an reading ability include giving warnings to children when wrong, giving guidance, giving praise to children, giving rewards or prizes to children who have good and good reading and giving assignments to repeat reading to children. And there are supporting factors that come from the students themselves such as having a good intellectual and having a high interest in improving the ability to read the Qur'an.